Eff ect of vitamin E isoforms on the primary intention Eff ect of vitamin E isoforms on the primary intention skin wound healing of diabetic rats - Bijo Elsy; Aijaz Ahmed Khan; Veena Maheshwari (Our Dermatology Online, 2017)
Introduction: Impaired wound healing events is a common complication in diabetes. One of the effective nutritional antioxidant on skin wound healing is vitamin E which contains saturated tocopherol and unsaturated tocotrienol forms. This present study is designed to explore the effect of different vitamin E isoforms on stitched skin wound in both healthy and diabetic rats. Materials and Methods: Forty eight albino rats were divided into eight groups; healthy control, diabetic control, healthy treated (d-α-tocopherol, d-δ-TRF and co-administrated) and diabetic treated (d-αtocopherol, d-δ-TRF and co-administrated). Diabetes was induced through single subcutaneous injection of alloxan at the dose of 100 mg/kg. Treated groups were administered d-a-tocopherol (200 mg/kg), d-δ-TRF (200 mg/kg) and co-administration (100 mg/kg of these two compounds each) orally and daily for three weeks. A horizontal skin incision was made on right mid-thigh region at 2.95 ± 0.17cm in length and wound was closed with an absorbable suture. Results: Histopathological and histomorphological results at the end of 3rd week revealed that the d-δ-TRF treated groups promote the regeneration and reorganization of epidermal and dermal components in healing of primary intention more effectively than the d-α-tocopherol and co-administrated groups. Conclusion: It is concluded that among different vitamin E isoforms the d-δ-TRF appears to be a more effective nutritional antioxidant on skin wound healing in both healthy and diabetics.